Keunggulan Balance Scorecard Sebagai Sistem Manajemen Strategis Yang Holistik - Lianto, Lianto (MABIS, 2011)
For many organizations, the Balanced Scorecard has evolved from a measurement tool to what Kaplan and Norton have described as a Strategic Management system. While the original intent of the Balanced Scorecard system was to balance historical financial numbers with the drivers of future value for the firm, as more and more organizations experimented with the concept they found it to be a critical tool in aligning short-term actions with their strategy. In this paper, Iâll explore each of the four perspectives of the Balanced Scorecard and identify the benefits of the scorecard in overwhelming the limitations of financial measurements.